The Relationship Between Resilience and Nurses’ Mental Health: A Systematic Review - Amani Istiqomah; Bangun Mukti Ardi (STIKep PPNI Jawa Barat, 2026)
Background: Nurses face chronic work-related stress burdens that lead to mental health problems such as depression, anxiety, stress, burnout, and sleep disorders, while suboptimal resilience levels may increase nurses’ mental health vulnerability. Objective: This systematic review aimed to synthesize recent evidence on the relationship between resilience and mental health outcomes among nurses. Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A structured search was conducted in Scopus, PubMed, ScienceDirect, and Web of Science to identify articles published in English between 2021 and 2025. Original quantitative studies that examined the association between resilience and mental health outcomes among nurses were included. Two reviewers independently screened the records, assessed eligibility, and resolved disagreements through discussion. Methodological quality was appraised using the Joanna Briggs Institute Critical Appraisal Checklist. Due to heterogeneity in study measures and outcomes, findings were synthesized narratively. Results: A total of 1319 records were identified, of which 10 studies met the inclusion criteria. Resilience was consistently associated with lower levels of depression, anxiety, psychological distress, burnout, and fatigue among nurses. Higher resilience was also associated with better psychological well-being, professional quality of life, occupational adaptation, and job satisfaction. Several studies suggested that resilience functioned as a mediating factor in the relationship between occupational stressors and mental health outcomes, while burnout also emerged as an important mediator. Conclusion: Resilience is consistently associated with more favorable mental health outcomes among nurses. However, the available evidence is limited to cross-sectional research, preventing causal inference. Strengthening resilience may represent a promising strategy to support nurses’ mental health, but future longitudinal and intervention studies are needed